Use of virtual reality in patient education program to reduce anxiety in upper gastrointestinal endoscopy: A randomized controlled trial - Surachet Siripongsaporn; Karn Yongsiriwit; Kittithat Tantitanawat; Sakkarin Chirapongsathorn (JGH Open, 2024)
Abstract Background and Aim Virtual reality (VR) provides an immersive image‐viewing experience that has recently been expanding its use in clinical medicine. We aimed to examine a patient education program by VR to reduce anxiety in patients undergoing esophagogastroduodenoscopy (EGD). Methods We conducted a randomized controlled trial and consecutively enrolled patients who had an indication for unsedated EGD with topical anesthesia. Patients were randomly assigned to use Oculus GO with three‐dimensionally specific software content (a stand‐alone VR headset) for patient education or standard patient education using oral information (the control group) before EGD. The primary outcome was the variation in anxiety scores before and after patient education programs. Results A total of 107 patients underwent EGD and received a VR (n = 58) and control (n = 49) patient education program. The mean anxiety score before starting the patient education program was 41.4 9.6 in the VR group and 41.9 7.7 in the control group. The mean anxiety score after the patient education program was 37.1 10.8 in the VR group and 38.9 8.07 in the control group (P‐value = 0.354). The anxiety score in the VR group decreased more than in the control group but was not significant. The recall questionnaire scores were higher in the VR group (4.70.4) than the control group (3.91, P‐value 0.001). Conclusion A virtual reality‐assisted patient education program before EGD did not significantly reduce anxiety but may provide more memory and understanding about the procedure to patients who underwent unsedated EGD.